HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERSONAL HYGIENE PENJAMAH MAKANAN DI WARUNG MAKAN DESA SADANG, TUBAN - Novita Rachma Salsabila; Fitri Komala Sari; Luthfiyah Nurlaela; Hidayatun Muyasyaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Personal hygiene in food handlers is the key to success in safe and healthy food processing. One of the factors that influence personal hygiene practices of food handlers is the level of knowledge and attitude. This study aims to determine the relationship between knowledge and attitude with Personal Hygiene Behavior of Food Handlers at the Food Stall in Sadang Village, Tuban. This study is a quantitative study with 31 respondents. Data were collected using instruments of knowledge questions, attitude questions and observation sheets that have been validated by experts. Data analysis used the chi-square test in SPSS software version 22 to determine the relationship between knowledge and attitude with personal hygiene of food handlers. The results of this study indicate that there is no relationship between the level of knowledge (p-value 0.272) with personal hygiene practices and there is a relationship between attitude (p-value 0.000) with personal hygiene practices. Therefore, further research is expected to have more valid and structured initial observation data so that the results of the study can describe field conditions more accurately.